2004
DOI: 10.1111/j.1600-0684.2004.00062.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a rhesus monkey model of asymptomatic tuberculosis

Abstract: Rhesus monkeys (RM) were inoculated intrabronchially with graded doses of Mycobacterium tuberculosis (MTB) strains Erdman and H37Rv in an effort to produce a model of asymptomatic tuberculosis infection. Erdman strain produced active disease within 7-11 weeks regardless of dose. Low doses of H37Rv resulted in asymptomatic infections; high doses produced active disease within 11 weeks. Over a 4-month period of post-inoculation study, MTB culture-filtrate protein (CFP)-stimulated bronchoalveolar lavage cells (BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 39 publications
4
59
0
2
Order By: Relevance
“…The early investigations during the Golden Age (17-21) specifically showed that M. tuberculosis infection in RM progresses rapidly, within 8 to 9 weeks after aerosol inhalation of the H37Rv strain administered at low doses of up to 62 CFU. In 2004, the Tulane NPRC established a model of asymptomatic, or latent, M. tuberculosis infection of RM (26). The investigators there revealed that RM are a good model for not only active TB but also asymptomatic TB when the investigators used lower doses (30 CFU) of the H37Rv strain.…”
Section: Rhesus Macaquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The early investigations during the Golden Age (17-21) specifically showed that M. tuberculosis infection in RM progresses rapidly, within 8 to 9 weeks after aerosol inhalation of the H37Rv strain administered at low doses of up to 62 CFU. In 2004, the Tulane NPRC established a model of asymptomatic, or latent, M. tuberculosis infection of RM (26). The investigators there revealed that RM are a good model for not only active TB but also asymptomatic TB when the investigators used lower doses (30 CFU) of the H37Rv strain.…”
Section: Rhesus Macaquesmentioning
confidence: 99%
“…A series of subsequent investigations were dedicated to macaque research to assess novel TB vaccines and drugs, as well as to gain an understanding of the pathogenesis of M. tuberculosis infection and reactivation. Figures 2 and 3 abridge the RM (13,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) and CM (10,15,25,(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59) models of experimental M. tuberculosis infection after the Golden Age, from 2001 to 2014.…”
Section: Historical Outlook On Macaque Modelsmentioning
confidence: 99%
“…The Erdman strain has also been used in rhesus and cynomolgus macaques by other research groups (17)(18)(19)(20)(21), and a comparison of BCG vaccination followed by high-dose M. tuberculosis strain Erdman challenge in these two species suggested that cynomolgus macaques had improved control of infection (22). There is evidence for LTBI in rhesus macaques using the H37Rv strain delivered at a low dose (23) or the less virulent strain CDC1551 strain delivered at higher doses and reactivation of CDC1551 LTBI by SIV (24). The route of challenge (aerosol versus bronchoscopic challenge) in rhesus macaques influences the distribution of disease but not the overall outcome of the infection (25).…”
mentioning
confidence: 99%
“…The nonhuman primate model of TB mimics all the pathological features of human TB and has the advantage of a large array of available immunologic reagents (3,8,10,11,26). Granulomas of the macaque model exhibit characteristics very similar to human tuberculous granulomas that include cavitation, calcification, caseous necrosis, and multinucleated giant cells within affected lung and lymph nodes.…”
mentioning
confidence: 99%